As questões de gênero, raça e classe em livros didáticos de Matemática: uma análise a partir da educação Ciência, Tecnologia e Sociedade – CTS - Sousa, André Cristovão (2023)
Among the contemporary guidelines that we open the paths for the deconstruction of patriarchy and monoculture, we do not teach, but as an anti-racist culture, we fear the necessary anti-colonial struggle of educational practices, defacing stereotypes that maintain the domination of class, race and gender, which amplifies inequalities and social injustices. For the natural sciences, there is still a challenge to decharacterize their static, unquestionable, and neutral aspect, since the sciences, specifically Mathematics, walk alongside the technological reality and its consequences for social and economic development. In this sense, the objective of the research was to identify the contributions of two textbooks - LD of Mathematics approved by PNLD, considering Education Science, Technology and Society - ECTS for the visibilities of gender, class and class quests. It is a qualitative, exploratory, and documentary study. The data are constituted from two textbooks of Mathematics "Praticando Matemática" and "Araribá: Mais Matemática". The results will show that, despite the advances in the discussions about the deconstruction of stereotypes and the insertion of concrete situations in reality for the STS education and integral formation of the subject, the textbooks still reproduce the European monoculture, making invisible the scientific and social contribution of blacks, women and indigenous people, or that encourages the reproduction of prejudices and discrimination. There are few mentions of specific situations that can lead to CTS education, being either a teacher or the main moving agent that can act so that education is based on the emancipation and freedom of the subject. It is considered that the discussions on the construction of gender and sexuality must advance so that there is a break with the binary that imposes the legitimacy of the dominance of one class over another, of one race over another or of one gender over another. Education must transgress the strategies of domination to train people against all forms of discrimination and prejudice, in order to advance towards the emancipation of two subjects. It is concluded that in the textbook collections analyzed, it can be said that there is a timid movement to include subjects who were made invisible and excluded, however, it is also clear that situations that reinforce stereotypes and discrimination are still present on the pages of textbooks.